2013
DOI: 10.5935/0103-5053.20130176
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Pharmaceuticals and Personal Care Product Residues in Surface and Drinking Water Samples by SPE and LC-ESI-MS/MS

Abstract: 0.99 for all compounds. Recoveries ranged from 65 and 120% with relative standard deviation (RSD) lower than 20%. The method was applied to the determination of PPCPs in samples of surface and drinking water for three months. PPCPs were detected at µg L-1 levels.]]>

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
0
8
0
4
Order By: Relevance
“…The evaluation of the toxicological impacts on the environment of these classes of pollutants is not a facile task. Despite the fact that the pollution burden is commonly found at low levels in the environment (e.g., in water bodies, in parts per billion or parts per trillion) [1][2][3] , it is verified the simultaneous occurrence of several different anthropic substances for a given contaminated sample. Therefore, the complications arising from the combined toxicological effects comprise an environmental concern of extreme relevance.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The evaluation of the toxicological impacts on the environment of these classes of pollutants is not a facile task. Despite the fact that the pollution burden is commonly found at low levels in the environment (e.g., in water bodies, in parts per billion or parts per trillion) [1][2][3] , it is verified the simultaneous occurrence of several different anthropic substances for a given contaminated sample. Therefore, the complications arising from the combined toxicological effects comprise an environmental concern of extreme relevance.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have demonstrated the presence of different organic pollutants in rivers and wastewaters (e.g., drugs, pesticides, herbicides, hormones, etc.) [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas últimas décadas os produtos farmacêuticos e cosméticos vem ganhando atenção no cenário ambiental pelos diversos relatos da ocorrência desses em águas superficiais, estações de esgoto e até mesmo em água potável, podendo assim considerá-los contaminantes emergentes de água (COMERO et al, 2013;NARBAITZ et al, 2013;SIMAZAKI et al, 2014;ZORITA et al, 2009;SILVEIRA et al, 2013).…”
Section: Presença De Fármacos Psicotrópicos No Ambienteunclassified
“…Seguindo a mesma tendência, em 2010, Frasco et al, utilizando ensaios in vitro com AChE isolada sugerem que a atividade da enzima deva ser utilizada como biomarcador de neurotoxicidade para metais, com exceção do níquel. Similarmente, a atividade da enzima AChE tem sido considerada um bom biomarcador de neurotoxicidade em peixes expostos a hidrocarbonetos policíclicos aromáticos (ALMEIDA et al, 2012;SILVA et al, 2013). Adicionalmente, a atividade da enzima colinesterase tem sido sugerida como um dos biomarcadores usados na avaliação de neurotoxicidade de peixes marinhos expostos a misturas complexas de poluentes (GRAVATO et al, 2010).…”
Section: Presença De Fármacos Psicotrópicos No Ambienteunclassified